Eksistensi Isomorphic Refinements dari Dua DC-Group yang Isomorfik - Mirna, Mirna; Rosjanuardi, Rizky; Yusnitha, Isnie (Mathematics Program Study, Universitas Pendidikan Indonesia (UPI), 2018)
ABSTRAK. Misalkan G = (G; C) adalah cyclically ordered group danA; B adalah subgrup dari G sedemikian sehingga memenuhi beberapakondisi. Berdasarkan asumsi tersebut, didenisikan dekomposisi produkleksikograk pada G dengan faktor A dan B, dinotasikan dengan G =A B. Lebih lanjut, suatu dekomposisi produk leksikograk padacyclically ordered group akan memiliki renement. Misalkan G dan Hadalah dc-group yang isomork, yang dinyatakan sebagai dekomposisiproduk leksikograk berhingga dari masing-masing subgrupnya, makaakan selalu memiliki isomorphic renements.Kata kunci: cyclically ordered group, dc-group, homomorsma padacyclically ordered group, dekomposisi produk leksikograk, renements.ABSTRACT. Let G = (G; C) be a cyclically ordered group and A; Bbe subgroups of G such that some conditions are satised. Based onthese assumptions, dened a lexicographic product decomposition on Gwith factors A and B, denoted by G = A B. Furthermore, a lexicographicproduct decomposition of the cyclically ordered group will havea renement. Let G and H be an isomorphic dc-group, expressed as thenite lexicographic product decomposition of each of its subgroups, thenit will always have isomorphic renements.Keywords: cyclically ordered group, dc-group, homomorphism of cyclicallyordered group, lexicographic product decomposition, renements.